1991
DOI: 10.1080/09553009114550161
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Response to Dominant Lethality of Mature (Class A) and Immature (Class B) Oocytes ofD. Melanogasterto Low Doses of Ionizing Radiation: Effects in Repair-proficient (yw) and Repair-deficient Strains (Mei 41D5and Mus 302D1)

Abstract: Mature oocytes (class A) and immature oocytes (class B) from a repair-proficient yw strain and two repair-deficient strains (mus 302D1 and mei 41D5) were initially X-irradiated with 0.02 Gy and subsequently treated at various time intervals with 2 Gy. They were tested for dominant lethality (early and late death). For each strain and stage the observed values were below those expected on the basis of additivity of the effects of the two irradiations given separately. These results indicate the existence of a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In other mutational studies, Fritz-Niggli and Schaeppi-Buechi (24) (25) or 5 cGy of 7-rays (26). Azzam et al (27) also found this same end point to be reducked in a normal human fibroblast line (AG1522) exposed to chronic radiation (4.25 Gy at 0.003 Gy/min) before being challenged immediately with 4.25 Gy given in less than 2 min.…”
Section: Worldwide Experments With Other End Pointsmentioning
confidence: 85%
“…In other mutational studies, Fritz-Niggli and Schaeppi-Buechi (24) (25) or 5 cGy of 7-rays (26). Azzam et al (27) also found this same end point to be reducked in a normal human fibroblast line (AG1522) exposed to chronic radiation (4.25 Gy at 0.003 Gy/min) before being challenged immediately with 4.25 Gy given in less than 2 min.…”
Section: Worldwide Experments With Other End Pointsmentioning
confidence: 85%
“…Therefore, DNA is protected from any physical or chemical impairment when the chromatin is unable to do so, consolidating the genomic material to produce a minute, more hydrodynamically-formed cell [18]. DNA repair systems are known to be present in oocytes, having their activity influenced in various ways: genetic and environmental [19,20].…”
Section: State Of Knowledgementioning
confidence: 99%
“…On the other hand, the distinct possibility that DNA repair in oocytes may be enabled by radiation damage is inferred in a paper by Fritz-Niggli and Schaeppi-Buech [19]. An adaptive response to the effects of low doses of X-rays (0.02 Gy prior to 2 Gy) was observed in Drosophila melanogaster oocytes, and suggested the existence of 'a repair stimulating effect' of low doses for both the repair-deficient strains, as well as for the highly radiosensitive mature oocytes.…”
Section: State Of Knowledgementioning
confidence: 99%
“…The induction of radioadaptive response was first reported by Olivieri et al (1984) who showed that the frequency of chromatid aberrations were down to 50% less than expected after exposure to 1.5 Gy of x-rays. Many articles have demonstrated radioadaptive response in plant cells (Cortes et al 1990), insects (Fritz-Niggli and Schaeppi-Buechi 1991), Chinese hamster V79 cells (Ikushima 1987(Ikushima , 1989a(Ikushima , 1989b, cultured human lymphocytes (Shadley and Wolff 1987;Wolff et al 1988;Sankaranarayanan et al 1989;Shadley and Wiencke 1989;Ghiassi-nejad et al 2002), embryonic and HeLa cells (Ishii and Watanabe 1996), occupationally exposed persons (Barquinero et al 1995;Gourabi and Mozdarani 1998), cultured animal lymphocytes (Wojcik and Tuschl 1990), and in vivo studies on laboratory animals (Bosi and Olivieri 1989;Cai and Liu 1990;Liu et al 1992;Farooqi and Kesavan 1993). However, there are reports indicating lack of radioadaptive response in cultured human lymphocytes (Mortazavi et al 2000;Mortazavi et al 2003b;Joksic and Petrovic 2004).…”
Section: Introductionmentioning
confidence: 99%